What explain capital structure determinants choices of Shariah firms? - Raja, Rehan; Adam Sa'ad, Auwal; Rosman, Romzie; Hye, Qazi Muhammad Adnan (AESS Publications, 2024)
This study aims to discover key capital structure determinants for the entire Shariah firms operating in dissimilar contexts. Moreover, it also estimates the adjustment speed for these firms to maintain targeted capital structures at all times. For this purpose, 321 Shariah firms that are operational in Saudi Arabia, Pakistan, the UAE, and Indonesia are nominated. The empirical analysis is conducted using 11 years, i.e., 2011-2021, of balanced Panel Data. The debt-to-asset and debt-to-equity ratios are used as variables of interest, whereas the asset tangibility ratio, current ratio, return on equity, size, non- debt-tax shield, inflation, and gross domestic product are used as explanatory variables. The robust estimator, i.e., Generalized Method of Moments (GMM), is executed to perform the analysis. The results show that the most important factors for Shariah- tagged firms are inflation, the gross domestic product, the asset ratio, the return on equity, the non-debt tax shield, and the lagged dependent variables. The important role of asset tangibility, lagged variables, and the presence of adjustment speed postulate that Shariah-tagged firms are following the provided guidelines of Dynamic Trade-Off theory to preserve capital structure. The findings are a new contribution to the limited empirical inquiries of Shariah firms’ capital structure and a fresh addition to Islamic Finance literature. Besides, the outcomes are also helpful for policymakers and assist them in developing an optimal model of capital structure for Shariah-tagged firms that decreases overall capital costs and enhances these firms’ market value.